Penetapan Kadar Kalsium Pada Kacang Hijau (Vigna Radiata L.) Secara Kompleksometri - Refdia Yola; Renatalia Fika (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2021)
Green beans (Vigna radiata L.) contain many nutrients needed by the body, one of which is calcium. In this study, a complexometric test was carried out to determine calcium levels in green beans (Vigna radiata L.). This titration was carried out directly with murexid indicator and using Na2EDTA as a titrant. The end point is indicated by a color change from pink to violet. From the research that has been done, the calcium level in green beans (Vigna radiata L.) is 0.220% w/w.